Identification of Mgenia fuscovaria (StÃ¥l)(Hemiptera: Cicadellidae), a vector of aster yellows disease on grapevines in South Africa, and differentiation from Mgenia angusta (Theron) by nucleotide sequences of the mitochondrial cytochrome oxidase I (cox1) gene - Pietersen, G.; Pietersen, Jnr, G.; Pietersen, I.; Stiller, M. (South African Journal of Enology and Viticulture, 2018)
Aster yellows phytoplasma (AY), only recently reported in South Africa and still limited in its distribution in the country, causes a serious disease of grapevine. A leafhopper, Mgenia fuscovaria (StÃ¥l)(Hemiptera: Cicadellidae), was shown to transmit AY to grapevine (Vitis vinifera L.) locally. A second Mgenia species, identified as Mgenia angusta (Theron), has also been found in vineyards in South Africa but has not been shown to transmit AY. M. angusta is morphologically similar to M. fuscovaria, but does differ regarding the size of the male sex organ and in the number of teeth of the blades making up the ovipositor. In this study, we determined the nucleotide sequence of the mitochondrial cytochrome oxidase I gene (cox1), commonly used in insect bar-coding, of a number of specimens of males, females and nymphs of both M. fuscovaria and M. angusta. No differences were observed between the cox1 sequences of the male, female and nymph specimens putatively assigned to any specific species, but some nucleotide sequence differences were observed between specimens of M. fuscovaria and M. angusta. These differences, however, were insufficient to allow the development of PCR systems specific to each species.